Transporte de sólidos em suspensão no estuário do Rio Pará - CARNEIRO, Adriel Guimarães (2018)
The focus of this work is to quantify suspended solids concentrations (CSLS) and suspended solids transport (TSLS) along the mixing zone of a tidal dominated Amazonian estuary. The Pará River Estuary (ERP) is located south of Marajó Island and receives discharge from the Tocantins River, Pará and other tributaries. Two oceanographic campaigns were conducted to collect suspended particulate matter (SPM) and turbidity. During a semidiurnal tide cycle, hourly bottom and surface samples were collected at four points in the estuary, for the dry and rainy period. CSLS determination was performed by linear correlation between SPM and turbidy. The results obtained indicate a lateral differentiation of ERP. The right margin exported solids in suspension to the adjacent seaward, while the left margin imported. TSLS on the right margin was more accentuated in the bottom layers, and lutoclin was observed at shallower depths. In the left margin, the TSLS did not present significant differences between the layers, and the lutoclin was deeper, in the dry and rainy period. The correlation between the bottom CSLS and along the water column was higher in the left margin. Indicating that about 80% of the CSLS in this margin comes from the resuspension of the material deposited in the substrate. The ERP was classified as bidirectional laterally. The left margin as vertically mixed and the right margin as vertically stratified.